ESSENCE AND FEATURES OF THE CRIMINAL ACTIVITY OF THE MARGINAL ADOLESCENT: MODERN CONDITION AND TRENDS - Y. Nesterov, Artyom (Scientific Journal of Pedagogy and Economics, 2020)
article presents the main problems of the theory and practice of criminal activity in the modern teenage environment. The statistical data of the Ministry of Internal Affairs of the Russian Federation and the Federal Penitentiary Service of Russia of the Ministry of Justice of the Russian Federation of criminal offenses committed from 2003 to the present period by juvenile offenders are given [as of June 1, 2020]. The author analyzes the features of the criminal youth subculture. Typologization is carried out according to the types of youth informal groups. The main causes of juvenile delinquency are identified and justified. Spectral analysis is carried out for these reasons (motives). The factors provoking crime in a teenage environment are determined. The author revealed that one of the negative conditions for the formation of delinquent and deviant behavior of adolescents is the early start of work. At present, adolescents from 14 years old are going through a process of socialization and familiarization with work in the conditions of transformation of socio-economic, political, sanctions relations. The transformation in Russia led to the use of various illegal forms, in particular related to the involvement of street children (10-15 years old and 16-18 years old) in the criminal business. The author determines that juvenile delinquency is primarily determined by the characteristics of the personality of the offender. The main thing in its consideration was the minority of the offender. Certain biological, psychological and mental changes in the structure of the personality are associated with it. Age determines a certain level of development of forces, intelligence, drives, and even the “physical” ability to commit certain crimes. Also, the author of the article determined that the process of socialization of an individual begins at an early age, when he begins to assimilate the roles that form his personal qualities. It is in childhood that any person is formed as a social being, he develops intelligence, the ability to analyze and generalize the surrounding phenomena, the ability to anticipate the possible consequences of his actions; such volitional qualities as perseverance, determination, self-control, activity, initiative are developed; self-awareness, self-esteem, desire for independence are formed. All this is closely related to the subsequent behavior of the personality of a minor offender. The author interprets such a basic concept as “criminal youth subculture”. The regional statistics of the Ministry of Internal Affairs of Russia on offenses as a consequence of the COVID-19 pandemic in Russia is given. All materials presented in the article do not contain information (information) related to state secrets of the Russian Federation.